Automated Performance Testing of End-to-End Streaming Solutions over HbbTV Architecture - Gavrilă, Cristinel; Kertész, Csaba Zoltán (IEEE, 2016)
This paper presents an automated test execution environment designed to analyze the accessibility, reliability and streaming performance of an end-to-end Hybrid broadcast broadband TV (HbbTV) solution. Its purpose is to provide the means for the TV providers to test their HbbTV solution by simulating real-world scenarios and online functioning in a local, oﬄine environment, before making it available for the end users. This way, common problems like server overload, poor streaming quality and HbbTV incorrect functionality can be foreseen and corrected.
Keywords: HbbTV; Automated testing; Streaming media; Web services; Network conditions simulation